Metanephric stromal tumor: An unusual presentation of a rare paediatric renal neoplasm - Nouha Ben Abdeljelil; Rim Hadhri; Manel Njima; Yosra Sghaier; Lassaad Sahnoun; Abdelfatah Zakhama (Wolters Kluwer Medknow Publications, 2018)
A 2-year-old boy with prenatal diagnosis of a malformation uropathy was referred to paediatric surgery department. On systemic examination, there were no palpable masses. An ultrasonography of abdomen with color Doppler, a renal artery angiographic and scintigraphy revealed a preostial aneurysm at the left renal artery. The patient had a left nephrectomy. Grossly, the specimen measured 75 mm × mm 50 × 20 mm with renal artery aneurysm measuring 30 mm × 35 mm. On cut section, the renal parenchyma contained a whitish tumor that measured 35 mm × 10 mm. Histopathologically, this tumor was diagnosed as metanephric stromal tumor.